Preliminary Study of Traffic Characteristics Based on Data Flow And Speed of Vehicles (Case Study of Nginden Road, Surabaya) - Hendrata Wibisana; Zetta R. Kamandang; Fithrie E (International Journal of Science, Engineering, and Information Technology, 2018)
An arterial road is a high capacity urban road used by various categories of vehicles. The arterial road characteristics composed of traffic flow, traffic density and speed of vehicles. Therefore, every arterial road has different characteristics depends on its type and actual data. In order to identify the characteristics of arterial road based on traffic density and speed of vehicles, this research implements a least square method into a case study in Surabaya assumed that the relationship of traffic density and vehicles speed is linear and the traffic characteristic model based on Greenshield. At the end, this research concludes that Nginden Road as case study has maximum vehicle speed at 26 km/h and traffic density at 166 pcu/km with the Greenshield model